Pathways to Improve Student Pharmacists’ Experience in Research - McClendon, Katie S. (Am J Pharm Educ, 2015)
Objective. To describe the implementation of a student research program and to provide outcomes from the initial 4 years’ experience. Design. Students conducted individual research projects in a 4-year longitudinal program (known as Pathway), with faculty member advising and peer mentoring. A prospective assessment compared perceptions of those who completed the Pathway program with those of students who did not. Descriptive statistics, t tests, and analysis of variance (ANOVA) were used. Assessment. The class of 2013 was the first to complete the Pathway program. In the Pathway assessment project, 59% (n=47) of students who responded reached self-set goals. Pathway students agreed that this research experience improved their ability to work/think independently, evaluate literature, and distinguish themselves from other students. Conclusion. The Pathway program helped students understand the research process and reach other self-set goals.